Comparison of systemic cytokine levels in patients with acute respiratory distress syndrome, severe pneumonia, and controls. Issue 1 (1st January 2000) - Bauer, Torsten T; Montón, Concepción; Torres, Antoni; Cabello, Hernan; Fillela, Xavier; Maldonado, Abel; Nicolás, Jose-Maria; Zavala, Elisabet
Abstract : BACKGROUND: The inflammatory response has been widely investigated in patients with acute respiratory distress syndrome (ARDS) and pneumonia. Studies investigating the diagnostic values of serum cytokine levels have yielded conflicting results and only little information is available for the differential diagnosis between ARDS and pneumonia. METHODS: Clinical and physiological data, serum concentrations of tumour necrosis factor (TNF)-α, interleukin (IL)-1β and IL-6, and quantitative cultures of lower respiratory tract specimens were obtained from 46 patients with ARDS and 20 with severe pneumonia within 24 hours of the onset of the disease and from 10 control subjects with no inflammatory lung disease. Cytokine concentrations were compared between groups and determinants in addition to the diagnosis were tested. RESULTS: Serum TNF-α levels were significantly higher in ARDS patients (67 (57) pg/ml) than in patients with severe pneumonia (35 (20) pg/ml; p = 0.031) or controls (17 (8) pg/ml; p = 0.007). For IL-1β and IL-6 the observed differences were not statistically significant between patients with ARDS (IL-1β: 34 (65) pg/ml; IL-6: 712 (1058) pg/ml), those with severe pneumonia (IL-1β: 3 (4) pg/ml, p = 0.071; IL-6: 834 (1165) pg/ml, p = 1.0), and controls (IL-1β: 6 (11) pg/ml, p = 0.359; IL-6: 94 (110) pg/ml, p = 0.262). TNF-α (standardised coefficient β = 0.410, p<0.001) and IL-1β (standardised coefficient β = 0.311, p = 0.006) were most strongly associated with the degree of lung injury, even when the diagnostic group was included in the statistical model. CONCLUSIONS: Serum TNF-α levels were higher in patients with ARDS than in those with severe pneumonia or in control subjects. Multivariate results suggest that the levels of systemic TNF-α and IL-1β reflect the severity of the lung injury rather than the diagnosis.